Composite alloy and preparation method thereof
By doping specific proportions of phosphorus, iron, chromium, nickel, molybdenum and mixed metal elements in cemented carbide, and using organic flux and discharge plasma sintering technology, the high cost and low purity in the existing technology are solved. The problem of this is to achieve the preparation of composite alloys with high hardness, high strength and high purity.
Patent Information
- Application Number
- CN202411668694.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In order to improve the comprehensive mechanical properties of cemented carbide in the prior art, doping a large number of other metal elements leads to a significant increase in the cost of preparing the composite alloy, and the failure to add flux is not conducive to improving the purity of the composite alloy and simplifying the preparation process.
Composite alloys are prepared by ball milling and discharge plasma sintering technology using components A including phosphorus, iron, chromium, nickel, molybdenum, and mixed metal elements and B components of organic flux.
The hardness, strength and purity of the composite alloy are improved, the preparation process is simplified, the cost is reduced, and the microstructure and mechanical properties of the alloy are improved.
Smart Images

Figure CN119464964A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgical materials, and in particular to a composite alloy and a preparation method thereof. Background Art
[0002] Cemented carbide is known as the "teeth of industry". It has excellent hardness, wear resistance and fracture toughness and is widely used in the field of industrial manufacturing. However, the performance of cemented carbide is mainly affected by the bonding phase. The development of the bonding phase is an important way to improve the comprehensive performance and service life of cemented carbide. In previous studies, Co was mainly used as a cemented carbide binder because of its low melting point, good wetting with the hard phase, and a certain solubility of the hard phase in Co. However, the Co binder is easy to soften at high temperatures, resulting in a significant reduction in the hardness, strength and corrosion resistance of the hard alloy material. If other metal elements can be doped into cemented carbide, it will help improve the microcrystalline structure of the composite alloy and improve the comprehensive mechanical properties of the composite alloy. However, which metal element to choose and the proportion of the metal elements are technical issues worthy of research and discussion.
[0003] Patent application CN104073734A discloses a nickel-chromium-iron-based composite material and a preparation method thereof. Calcium oxide, germanium oxide, silicon dioxide, titanium boride, cerium oxide, aluminum oxide and cobalt oxide are used as additives. The nickel-chromium-iron alloy is melted, and the above additives are added to the smelted alloy. After process treatment, a nickel-chromium-iron-based composite material with refined grains and high-temperature oxidation resistance is prepared. However, the content of doped additives in the above composite material is too high, which increases the manufacturing cost; in addition, no flux is added during the preparation process of the above composite material, which is not conducive to improving the purity of the prepared composite alloy and simplifying the preparation process of the composite alloy.
[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a composite alloy and a preparation method thereof, which is used to solve the problem that in the prior art, in order to improve the comprehensive mechanical properties of cemented carbide, a large amount of other metal elements are doped, resulting in a significant increase in the cost of preparing the composite alloy; in addition, what kind of flux to add to further improve the purity of the composite alloy and simplify the preparation industry is also a technical problem that needs to be solved urgently.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A composite alloy, comprising component A and component B, with the remainder being inevitable impurities; in terms of mass percentage, component A comprises 4.9-5.0%wt of phosphorus, 52-55%wt of iron, 13-14%wt of chromium, 1.5-2.0%wt of nickel and 1-2%wt of molybdenum;
[0008] The B component includes mixed metal elements and organic flux; in terms of mass percentage, the B component includes 0.4-0.45%wt of manganese, 0.1-0.15%wt of copper, 0.05-0.1%wt of titanium, 0.02-0.03%wt of calcium, 0.02-0.03%wt of magnesium, 0.02-0.03%wt of aluminum and 0.1-0.3%wt of organic flux.
[0009] Furthermore, the preparation method of the organic flux comprises the following steps:
[0010] A1, charcoal and deionized water are evenly mixed to obtain a mixed solid-liquid; the mixed solid-liquid is heated to 50-60°C, 1-5 mol / L sodium hydroxide solution is added dropwise to the mixed solid-liquid, and then the mixture is kept warm at 110-120°C for 2-3 hours to obtain an alkaline charcoal mixed liquid;
[0011] A2. Add boric acid to the alkalized charcoal mixture, then heat to 150-160° C., carry out esterification reaction for 2-3 hours, and then filter to collect the solid; wash the solid with deionized water and vacuum dry to constant weight to obtain an organic flux.
[0012] Furthermore, in step A1, the ratio of charcoal to deionized water is 20-30 g:100 mL, the amount of sulfuric acid is 10 mL, and the amount of boric acid is 2-5 g.
[0013] As another aspect of the present invention, a method for preparing a composite alloy comprises the following steps:
[0014] B1. Prepare various materials according to the composition of the metal elements and organic flux of components A and B; mix the above materials evenly, add them into a ball mill and grind them to obtain mixed metal powder;
[0015] B2. The mixed metal powder is loaded into a graphite mold and pressed to obtain a pre-pressed part; the vacuum degree of the spark plasma sintering furnace is set to 30Pa, and then the pre-pressed part is placed in the spark plasma sintering furnace for heating and sintering, and heat preservation to obtain a composite alloy.
[0016] Furthermore, in step B1, the ball milling speed is 1000-2000 r / min, the ball milling time is 15-25 h, and the ball-to-material ratio is 10:1.
[0017] Furthermore, in step B2, the sintering temperature is increased from room temperature to 1000-1100°C, with a heating rate of 30-60°C / min; the sintering pressure is 30-50MPa, and the insulation time is 10-15min.
[0018] The present invention has the following beneficial effects:
[0019] 1. The composite alloy matrix prepared by the present invention is an iron-chromium-nickel-molybdenum alloy doped with phosphorus, and a certain amount of mixed metal elements and organic flux are doped in the above matrix; a small amount of impurities exist in the above composite alloy, specifically carbon, hydrogen, nitrogen and oxygen elements. The impurities mainly come from oxides produced during the preparation of the composite alloy, gases and moisture adsorbed on the surface of the metal material. The trace mixed metal elements doped in the above matrix include manganese, copper, titanium, calcium, magnesium and aluminum. The content of the added mixed metal elements is small and the content is relatively uniform, forming a highly mixed microstructure. Such a mixed structure can improve the physical properties of the composite alloy, including improving the hardness and strength of the composite alloy.
[0020] 2. In the process of alloy smelting, charcoal can be used as an organic flux; as an organic flux, charcoal can improve the fluidity of metals during the metal smelting process. Since the composite alloy prepared by the present invention contains multiple mixed metal elements, adding a small amount of boric acid flux can form a complex with each metal ion, thereby enhancing the binding force between the various metal elements and promoting the uniform distribution of metal particles and grain refinement. The present invention alkalizes the charcoal in advance to activate the reaction activity of the charcoal itself; then the hydroxyl functional groups in the charcoal are used to undergo an esterification reaction with the boric acid flux to obtain a composite organic flux. Observation Figure 2 and Figure 3 The electron microscope photo of the composite alloy prepared in the present invention shows that the composite alloy particles prepared in the present invention are all in the micron level, and the diameter of the tiny particles is about 3μm; the microscopic morphology of the grains is granular or thin strips, and the distribution is relatively uniform. The fine grains can improve the strength and hardness of the prepared composite alloy. In addition, the organic components in the organic flux can generate highly soluble metal hydroxides with the oxides on the surface of the composite alloy, and the content of the oxides on the surface of the composite alloy is reduced by oxygen absorption and decomposition, which helps to improve the purity of the prepared composite alloy.
[0021] 3. In addition to doping a certain amount of phosphorus in the prepared alloy, the present invention also dopes a certain amount of phosphorus in the organic flux; phosphorus can form a corresponding lattice structure or crystal layer boundary, and doping with phosphorus can improve the plastic deformation ability of the prepared composite alloy, making the alloy material easier to process. The present invention adopts a powder metallurgy method to prepare the composite alloy, and its specific process flow includes preparing mixed powder, pressing and sintering; the spark plasma sintering technology used has the advantages of rapid sintering and adjustable microstructure, which can improve the sintering activity of the composite alloy, thereby facilitating the preparation of ultrafine-grained cemented carbide. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 The X-ray diffraction pattern of the composite alloy prepared in Example 2 of the present invention;
[0024] Figure 2 and Figure 3 All are electron microscope photos of the composite alloy prepared in Example 2 of the present invention;
[0025] Figure 4 This is the energy spectrum of the composite alloy prepared in Example 3 of the present invention;
[0026] Figure 5 This is a fluorescence image of the composite alloy prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] This embodiment provides a method for preparing an organic flux for a composite alloy, comprising the following steps:
[0030] A1. Weigh 20 g of charcoal and 100 mL of deionized water into a 250 mL four-necked flask and mix well to obtain a mixed solid-liquid solution; then heat the four-necked flask to 50 ° C using an oil bath method; then drop 10 mL of 1 mol / L sodium hydroxide solution into the four-necked flask, then heat the four-necked flask to 110 ° C, keep warm for 2 hours, and obtain an alkalized charcoal mixed solution.
[0031] A2. A four-necked flask is equipped with a reflux device, 2g of boric acid is added to the four-necked flask, and then the temperature of the four-necked flask is raised to 150°C. With stirring at 100r / min, the alkalized charcoal mixture undergoes esterification reaction for 2h, and then filtered to collect the solid. The solid is washed with deionized water and vacuum dried to constant weight to obtain an organic flux.
[0032] Example 2
[0033] This embodiment provides a method for preparing an organic flux for a composite alloy, comprising the following steps:
[0034] A1. Weigh 25 g of charcoal and 100 mL of deionized water into a 250 mL four-necked flask and mix well to obtain a mixed solid-liquid mixture; then heat the four-necked flask to 56 ° C using an oil bath method; then drop 10 mL of 3 mol / L sodium hydroxide solution into the four-necked flask, then heat the four-necked flask to 115 ° C, keep the temperature for 2.4 h, and obtain an alkaline charcoal mixed solution.
[0035] A2. A four-necked flask was equipped with a reflux device, 3 g of boric acid was added to the four-necked flask, and then the temperature of the four-necked flask was raised to 155°C. With stirring at 150 r / min, the alkalized charcoal mixture was esterified for 2.6 hours, and then filtered to collect the solid. The solid was washed with deionized water and vacuum dried to constant weight to obtain an organic flux.
[0036] Example 3
[0037] This embodiment provides a method for preparing an organic flux for a composite alloy, comprising the following steps:
[0038] A1. Weigh 30 g of charcoal and 100 mL of deionized water into a 250 mL four-necked flask and mix well to obtain a mixed solid-liquid mixture; then heat the four-necked flask to 60 ° C using an oil bath method; then drop 10 mL of 5 mol / L sodium hydroxide solution into the four-necked flask, then heat the four-necked flask to 120 ° C, keep warm and react for 3 hours to obtain an alkalized charcoal mixed solution.
[0039] A2. A four-necked flask is equipped with a reflux device, 5 g of boric acid is added to the four-necked flask, and then the temperature of the four-necked flask is raised to 160°C. With stirring at 200 r / min, the alkalized charcoal mixture undergoes esterification for 3 hours, and then filtered to collect the solid. The solid is washed with deionized water and vacuum dried to constant weight to obtain an organic flux.
[0040] Example 4
[0041] This embodiment provides a method for preparing a composite alloy, comprising the following steps:
[0042] B1. According to the mass percentage, component A includes 4.9%wt of phosphorus, 52%wt of iron, 13%wt of chromium, 1.5%wt of nickel and 1%wt of molybdenum; component B is a mixed metal element and an organic flux prepared in Example 3. According to the mass percentage, component B includes 0.4%wt of manganese, 0.1%wt of copper, 0.05%wt of titanium, 0.02%wt of calcium, 0.02%wt of magnesium, 0.02%wt of aluminum and 0.1%wt of the organic flux prepared in Example 3. Prepare various materials according to the mass percentage of each metal element and organic flux, mix the above materials evenly, and then add them into a planetary ball mill for ball milling to obtain a mixed metal powder; wherein the ball milling speed of the planetary ball mill is 1000r / min, the ball milling time is 15h, and the ball-to-material ratio is 10:1.
[0043] B2. The mixed metal powder is placed in a graphite mold and pressed into shape at a pressing pressure of 100 MPa and a pressing time of 10 min to obtain a pre-pressed part. The pre-pressed part is then placed in a spark plasma sintering furnace for sintering. The spark plasma sintering furnace is set to a vacuum degree of 30 Pa; the sintering temperature is increased from room temperature to 1000°C at a heating rate of 30°C / min. The sintering pressure of the spark plasma sintering furnace is 30 MPa and the holding time is 10 min to obtain a composite alloy.
[0044] Example 5
[0045] This embodiment provides a method for preparing a composite alloy, comprising the following steps:
[0046] B1. According to the mass percentage, component A includes 4.95%wt of phosphorus, 53%wt of iron, 13.4%wt of chromium, 1.8%wt of nickel and 1.6%wt of molybdenum; component B is a mixed metal element and an organic flux prepared in Example 3. According to the mass percentage, component B includes 0.42%wt of manganese, 0.12%wt of copper, 0.08%wt of titanium, 0.025%wt of calcium, 0.025%wt of magnesium and 0.025%wt of aluminum and 0.2%wt of the organic flux prepared in Example 3; prepare various materials according to the mass percentage of each metal element and the organic flux, mix the above materials evenly, and then add them into a planetary ball mill for ball milling to obtain a mixed metal powder; wherein the ball milling speed of the planetary ball mill is 1500r / min, the ball milling time is 20h, and the ball-to-material ratio is 10:1.
[0047] B2. The mixed metal powder is placed in a graphite mold and pressed into shape at a pressing pressure of 150 MPa and a pressing time of 12 min to obtain a pre-pressed part. The pre-pressed part is then placed in a spark plasma sintering furnace for sintering. The spark plasma sintering furnace is set to a vacuum degree of 30 Pa. The sintering temperature is increased from room temperature to 1050°C at a heating rate of 40°C / min. The sintering pressure of the spark plasma sintering furnace is 45 MPa and the holding time is 12 min to obtain a composite alloy.
[0048] Example 6
[0049] This embodiment provides a method for preparing a composite alloy, comprising the following steps:
[0050] B1. According to the mass percentage, component A includes 5.0%wt of phosphorus, 55%wt of iron, 14%wt of chromium, 2.0%wt of nickel and 2%wt of molybdenum. Component B is a mixed metal element and an organic flux prepared in Example 3. According to the mass percentage, component B includes 0.45%wt of manganese, 0.15%wt of copper, 0.1%wt of titanium, 0.03%wt of calcium, 0.03%wt of magnesium and 0.03%wt of aluminum and 0.3%wt of the organic flux prepared in Example 3; prepare various materials according to the mass percentage of each metal element and organic flux, mix the above materials evenly, and then add them into a planetary ball mill for ball milling to obtain a mixed metal powder; wherein the ball milling speed of the planetary ball mill is 2000r / min, the ball milling time is 25h, and the ball-to-material ratio is 10:1.
[0051] B2. The composite metal powder is loaded into a graphite mold and pressed into shape at a pressing pressure of 200 MPa and a pressing time of 15 min to obtain a pre-pressed part. The pre-pressed part is then placed in a spark plasma sintering furnace for sintering. The spark plasma sintering furnace is set to a vacuum degree of 30 Pa. The sintering temperature is increased from room temperature to 1100°C at a heating rate of 60°C / min. The sintering pressure of the spark plasma sintering furnace is 50 MPa and the holding time is 15 min to obtain a composite alloy.
[0052] Comparative Example 1
[0053] Compared with the composite alloy prepared in Example 6, the organic flux was replaced by charcoal of equal mass in this comparative example.
[0054] Comparative Example 2
[0055] Compared with the composite alloy prepared in Example 6, no mixed metal elements were added to the composite alloy in this comparative example, and component B was only an organic fluxing agent.
[0056] Comparative Example 3
[0057] Compared with the composite alloy prepared in Example 6, the pre-pressed part is sintered by using radiation heating instead of spark plasma sintering.
[0058] Performance Test:
[0059] 1. The hardness of the composite alloys prepared in Examples 4-6 and Comparative Examples 1-3 was measured in turn using a micro Vickers hardness tester; wherein the measuring load was 100 g and the loading time was 10 s. The hardness values of the composite alloys prepared in Examples 4-6 and Comparative Examples 1-3 were measured three times, and the average value was calculated each time.
[0060] 2. The composite alloys prepared in Examples 4-6 and Comparative Examples 1-3 were tested for tensile properties using an electronic universal testing machine to obtain their tensile strength and yield strength values. The tensile temperature was 700°C, the tensile rate was 0.12 mm / min, the gauge length was 10 mm, and the gauge section cross-sectional area was 3 mm×1 mm. The specific test results are shown in Table 1:
[0061] Table 1. Sample performance test data
[0062]
[0063] Data Analysis:
[0064] Comparative analysis of the data in Table 1 shows that the composite alloys prepared in Examples 4-6 of the present invention have excellent mechanical properties, as shown by high values of microhardness, tensile strength and yield strength. However, in Comparative Example 2, due to the lack of the addition of mixed metal elements, the mechanical properties of the composite alloy were significantly reduced, as shown by a significant decrease in the values of microhardness, tensile strength and yield strength. In Comparative Example 1, the high-efficiency organic flux was replaced, and in Comparative Example 3, radiation heating was used instead of spark plasma sintering, which were not conducive to the formation of a composite alloy structure with uniform distribution and grain refinement, thereby reducing the comprehensive mechanical properties of the prepared composite alloy, as shown by a decrease in the values of microhardness, tensile strength and yield strength.
[0065] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0066] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0067] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A composite alloy, characterized in that: It comprises component A and component B, and the balance is inevitable impurities; in terms of mass percentage, component A comprises 4.9-5.0%wt of phosphorus, 52-55%wt of iron, 13-14%wt of chromium, 1.5-2.0%wt of nickel and 1-2%wt of molybdenum; The B component includes mixed metal elements and organic flux; In terms of mass percentage, component B includes 0.4-0.45%wt manganese, 0.1-0.15%wt copper, 0.05-0.1%wt titanium, 0.02-0.03%wt calcium, 0.02-0.03%wt magnesium, 0.02-0.03%wt aluminum and 0.1-0.3%wt organic flux.
2. A composite alloy according to claim 1, characterized in that: The preparation method of the organic flux comprises the following steps: A1, charcoal and deionized water are evenly mixed to obtain a mixed solid-liquid; the mixed solid-liquid is heated to 50-60°C, 1-5 mol / L sodium hydroxide solution is added dropwise to the mixed solid-liquid, and the mixture is kept warm at 110-120°C for 2-3 hours to obtain an alkaline charcoal mixed liquid; A2. Add boric acid to the alkalized charcoal mixture, then heat to 150-160° C., carry out esterification reaction for 2-3 hours, and then filter to collect the solid; wash the solid with deionized water and vacuum dry to constant weight to obtain an organic flux.
3. A composite alloy according to claim 2, characterized in that: In step A1, the usage ratio of charcoal and deionized water is 20-30 g:100 mL, the usage of sodium hydroxide solution is 10 mL, and the usage of boric acid is 2-5 g.
4. A method for preparing a composite alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: B1. Prepare various materials according to the composition of the metal elements and organic flux of components A and B; mix the above materials evenly, add them into a ball mill and grind them to obtain mixed metal powder; B2. The mixed metal powder is loaded into a graphite mold and pressed to obtain a pre-pressed part; the vacuum degree of the spark plasma sintering furnace is set to 30Pa, and then the pre-pressed part is placed in the spark plasma sintering furnace for heating and sintering, and heat preservation to obtain a composite alloy.
5. The method for preparing a composite alloy according to claim 4, characterized in that: In step B1, the ball milling speed is 1000-2000 r / min, the ball milling time is 15-25 h, and the ball-to-material ratio is 10:
1.
6. The method for preparing a composite alloy according to claim 4, characterized in that: In step B2, the sintering temperature is increased from room temperature to 1000-1100°C, with a heating rate of 30-60°C / min; the sintering pressure is 30-50MPa, and the insulation time is 10-15min.
Citation Information
Patent Citations
Nickel-chromium-iron compound material and preparation method thereof
CN104073734A